Loving Yourself to Forgive: The Influence of Self-Compassion on Forgiveness Among College Students - Yoezer Galen Darian Samson; Keshia Irene Muliawan; Nixie Aurelia Liem; Xi Yang Chen; Yusak Novanto (Flourishing Journal, 2026)
Self-compassion is regarded as a psychological resource that enables individuals to respond to failure and painful experiences with greater kindness toward themselves, emotional balance, and acceptance. At University X, which upholds Christian values such as love and forgiveness, this study examined the effect of self-compassion on forgiveness among undergraduate students. This study employed a quantitative, non-experimental, correlational design with a cross-sectional approach, involving 202 undergraduate students selected through purposive sampling. Data were collected using the Self-Compassion Scale and the Heartland Forgiveness Scale. The data were analyzed using descriptive statistics, bivariate correlation analysis, and simple linear regression. The results revealed a significant positive relationship between self-compassion and forgiveness (r = .721), with self-compassion accounting for 51.6% of the variance in forgiveness (R² = .516). These findings indicate that students with higher levels of self-compassion are more likely to demonstrate greater forgiveness. Therefore, counseling and student development programs that focus on cultivating self-compassion may serve as an effective strategy for enhancing students' capacity for forgiveness. Abstrak Self-compassion dipandang sebagai salah satu sumber daya psikologis yang memungkinkan individu merespons kegagalan dan pengalaman menyakitkan dengan sikap yang lebih penuh kasih, seimbang secara emosional, dan penuh penerimaan. Di Universitas X yang menjunjung tinggi nilai-nilai Kristiani, seperti kasih dan pengampunan, penelitian ini bertujuan untuk menguji pengaruh self-compassion terhadap forgiveness pada mahasiswa. Penelitian ini menggunakan desain kuantitatif non-eksperimental dengan pendekatan korelasional dan rancangan cross-sectional yang melibatkan 202 mahasiswa yang dipilih menggunakan teknik purposive sampling. Instrumen yang digunakan adalah Self-Compassion Scale dan Heartland Forgiveness Scale. Data dianalisis menggunakan statistik deskriptif, uji korelasi bivariat, dan analisis regresi linear sederhana. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara self-compassion dan forgiveness (r = 0,721), dengan self-compassion menjelaskan 51,6% variasi forgiveness (R² = 0,516). Temuan ini menunjukkan bahwa mahasiswa dengan tingkat self-compassion yang lebih tinggi cenderung memiliki kemampuan memaafkan yang lebih baik. Oleh karena itu, pengembangan program konseling dan pembinaan mahasiswa yang berfokus pada peningkatan self-compassion dapat menjadi salah satu strategi untuk mendukung peningkatan self-compassion, guna meningkatkan tingkat forgiveness pada mahasiswa.